Biomarkers of Rotator Cuff Disease Severity and Repair Healing. Issue 9 (September 2018) - Ma, Jinjin; Piuzzi, Nicolas S.; Muschler, George F.; Iannotti, Joseph P.; Ricchetti, Eric T.; Derwin, Kathleen A.
Abstract : Identifying biomarkers of disease severity and prognostic factors for healing after rotator cuff repair would allow improved clinical decision-making about the treatment of patients with rotator cuff pathologies and possibly identify targets for therapeutic intervention to promote healing. The state of investigations to identify biomarkers of disease severity or repair success has been neither systematic nor standardized. Clinical studies to date have been largely exploratory, with small sample sizes and univariate analyses. Current evidence shows that inflammatory biomarkers (interleukin 1 [IL-1β], interleukin 1 receptor antagonist [IL-1ra], tumor necrosis factor alpha [TNF-α], cyclooxygenase-2 [COX-2], inducible nitric oxide synthase [iNOS]) and matrix remodeling biomarkers (biglycan, aggrecan, and members of the collagen and matrix metalloproteinase [MMP] families) were found to be significantly associated with rotator cuff disease severity. Similarly, inflammatory biomarker COX-2 and matrix remodeling biomarkers (biglycan, tissue inhibitor of metalloproteinase [TIMP]-1, and members of the collagen and MMP families) were found to be significantly associated with rotator cuff retears. Future studies investigating biomarkers of rotator cuff disease severity and healing should be standardized and should employ sample sizes large enough to allow for adequate power and multivariate analyses. Genetic and cellular biomarkers should be investigated, in addition to the more typical biochemical and structural factors. Progress would be greatly facilitated by forming a consortium of experts to define a strategic approach to biomarker research in rotator cuff disease and repair.